The authorship and type locality of Melanocorypha leucoptera (Aves: Alaudidae) - Mlíkovský, Jiří (Zootaxa, 2013)
The White-winged Lark is a monotypic bird species of Middle Asian steppes (Vaurie 1959; Alström et al. 2004; see Cowan 2006, 2007 for the term 'Middle Asia'). It was called Alauda (or Melanocorypha) sibirica J.F. Gmelin (1789: 799) until Gyldenstolpe (1926: 22) observed that Tanagra siberica Sparrman (1786: pl. 19) is a junior synonym of Melanocorypha yeltoniensis (Forster, 1768: 350) and Hartert and Steinbacher (1933: 103) argued that sibirica J.F. Gmelin is preoccupied in Melanocorypha Boie (1828: col. 322) by siberica Sparrman. Hartert and Steinbacher (1933) thus suggested that White-winged Lark should be called Melanocorypha leucoptera (Pallas "1831" = 1811: 518), which they believed to be the next oldest available synonym (see Hartert 1904: 211).